Predictive coding in agency detection - Andersen, Marc (Religion, brain & behavior, 2019)
Agency detection is a central concept in the cognitive science of religion (CSR). Experimental studies, however, have so far failed to lend support to some of the most common predictions that follow from current theories on agency detection. In this article, I argue that predictive coding, a highly promising new framework for understanding perception and action, may solve pending theoretical inconsistencies in agency detection research, account for the puzzling experimental findings mentioned above, and provide hypotheses for future experimental testing. Predictive coding explains how the brain, unbeknownst to consciousness, engages in sophisticated Bayesian statistics in an effort to constantly predict the hidden causes of sensory input. My fundamental argument is that most false positives in agency detection can be seen as the result of top-down interference in a Bayesian system generating high prior probabilities in the face of unreliable stimuli, and that such a system can better account for the experimental evidence than previous accounts of a dedicated agency detection system. Finally, I argue that adopting predictive coding as a theoretical framework has radical implications for the effects of culture on the detection of supernatural agency and a range of other religious and spiritual perceptual phenomena.